Parameters for quality assurance of fire safety design in high-rise buildings - Ono, Rosaria (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents the development and results of a research project which aimed to establish design guidelines for fire safety in buildings, including both conceptual and practical issues. Some concepts are clarified, based on the requirements from fire codes and standards, in order to enable designers to discuss, argue and contribute for the improvement of the fire safety measures, as well as to apply them in an adequate and integrated way to building design.